2019
DOI: 10.3390/metabo9110267
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction: New Insight from the Metabolomic Approach

Abstract: Recognizing intrauterine growth restriction (IUGR) is a matter of great concern because this condition can significantly affect the newborn’s short- and long-term health. Ever since the first suggestion of the “thrifty phenotype hypothesis” in the last decade of the 20th century, a number of studies have confirmed the association between low birth weight and cardiometabolic syndrome later in life. During intrauterine life, the growth-restricted fetus makes a number of hemodynamic, metabolic, and hormonal adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 69 publications
0
32
1
14
Order By: Relevance
“…Controversial information is evidenced in the literature concerning candidate metabolites for IUGR-AGA discrimination, with abnormal amino acid metabolism, glucose intolerance and limited insulin resistance being an important finding 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Controversial information is evidenced in the literature concerning candidate metabolites for IUGR-AGA discrimination, with abnormal amino acid metabolism, glucose intolerance and limited insulin resistance being an important finding 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent metabolomics results in IUGR [5,47], even in relation to gut dysbiosis [48] and evaluating neonatal urines [49,50], and in GDM [51][52][53] are currently available in literature.…”
Section: Metabolomics In Obstetricsmentioning
confidence: 99%
“…An interesting review [ 4 ] showed that metabolomic studies regarding the IUGR condition clearly differentiate between IUGR babies and controls and, despite all limitations, suggest an “early” pattern of glucose intolerance, insulin resistance, catabolite accumulation, disrupted amino acid metabolism and abnormal fetal liver function.…”
Section: Intrauterine Growth Restriction (Iugr)mentioning
confidence: 99%